Studying the effect of matric suction on the bearing capacity of footing on partially saturated sandy soil (Damascus University Journal for engineering sciences, 2025)
In this research the experimental method was adopted on samples of sandy soil taken from the city of Tartous (Al-Hamidiya village), and the aim is toReceived: 4/4/2023Accepted: 20/6/2023 Copyright:Damascus University- Syria, The authors retain the copyright under aCC BY- NC-SAstudy the effect of matric suction on the bearing capacity of footing on partially saturated sandy soil. To achieve the aim of the  research, experiments were conducted for the basic Physical properties of the soil, and a series of Laboratory loading tests were conducted for a model footing atop sandy soil for different values of matric suction, matric suction were measured and soil water characteristics curve (SWCC) was determined using filter paper technique. The results were analyzed and discussed, and The results of experimental work demonstrate that matric suction have a clear effect on the bearing capacity, and the values of the increase ranged between [3.2-9] times bearing capacity in the saturation state. The results showed that matric suction have a clear effect on the failure mechanism of the tested soil
Keywords: matric suction; sandy soil; footing